Декоративне малярство в архітектурному середовищі Ялти 1880-х – 1910-х рр. - Виноградов, В. (Культура народов Причерноморья, 2013)
В статье рассматриваются особенности украшения гражданской и жилой архитектуры Ялты произведениями декоративной живописи в период модерна. Выявляются мотивы фасадного и интерьерного декора. Анализируется построение схем росписи плоскостей архитектуры чистого модерна и стилизацй, в ориентальном духе. Описываются средства художественной выразительности и техники выполнения У статті розглядаються особливості оздоблення громадської та житлової архітектури Ялти творами декоративного малярства у період модерну. Виявляються мотиви фасадного та інтер’єрного оздоблення. Аналізується будова схем розпису площин архітектури чистого модерну і стилізацій, зокрема, в орієнтальному дусі. Описуються засоби художньої виразності і техніки виконання. The article focuses on the embellishment of public and residential architecture in Yalta with works of decorative art during the modernism period. The new style that had been developing at that time heavily influenced motives and patterns of ornaments in decorative painting of the period. The author believes that the motives of facade and interior decoration demonstrate a clear interaction of regional and pan-European art processes. He offers a structural analysis of various schemes of surface painting in the pure modernist architecture as well as in its stylizations, particularly in orientalism. Passion for everything «oriental» was equalled to enthusiasm for all things Asian and seen as synonymous to exotic, mysterious, genuine and profound. Unlike ornamental mural schemes painted in the oriental style, ornamented schemes in the modernist works were mainly depicting flora. Their origin was mostly traced to applied graphic design. Indeed it was the typography of the late XIX - early XX centuries that had led to emergence of a large number of motives that later were picked up by easel painting and decorative arts. Applied decorative painting associated with artistic wood curving and based upon it was effectively used as a way of ornamental embellishment in Yalta’s interiors of the late XIX – early XX centuries. Decorative painting as an ornamenting way was used in the interiors of Massandra Palace in the form of panels and executed in watercolor on wood surfaces of planes and doorways lunettes. Despite the limited amount of source material on decorative painting , the graphic nature of the compositions and the presence of painting in buildings of different styles and trends indicate widespread use of this type of decoration inYalta in the mentioned period.